1993
DOI: 10.1111/j.1464-5491.1993.tb02002.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Increase in the Prevalence of Known Diabetes in a Sample of an Urban Population in Greece

Abstract: It is accepted that the prevalence of known diabetes mellitus has increased in some countries, although the available data are incomplete and sometimes anecdotal. In 1974 a sample of the urban population (n = 21,410) in a suburb of Athens (Greece) was evaluated for the prevalence of known diabetes mellitus. The study was repeated 17 years later in the same area under the same conditions and methodology on 12,836 randomly selected inhabitants (both sexes, all ages). Visiting nurses contacted the inhabitants at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
4
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 7 publications
2
32
4
4
Order By: Relevance
“…However, screening of selected groups of the general population and the non-random, non-populationbased nature of most relevant studies have given rise to wide variations of the reported DM prevalence in Greece in previous studies. [16][17][18][19][20][21] The strengths of the present study are: i) a large number of subjects was evaluated in a door-to-door manner by experienced physicians who visited, interviewed, and collected data at their homes; ii) the participants were representative of the total adult target population of the studied areas and, most importantly, of the Greek adult population; iii) a high participation rate was achieved. On the other hand, this study is not without limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, screening of selected groups of the general population and the non-random, non-populationbased nature of most relevant studies have given rise to wide variations of the reported DM prevalence in Greece in previous studies. [16][17][18][19][20][21] The strengths of the present study are: i) a large number of subjects was evaluated in a door-to-door manner by experienced physicians who visited, interviewed, and collected data at their homes; ii) the participants were representative of the total adult target population of the studied areas and, most importantly, of the Greek adult population; iii) a high participation rate was achieved. On the other hand, this study is not without limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The development of type 2 DM is influenced by attained age and has been demonstrated in previous studies. [16][17][18][19][20][21][23][24][25][26] With regard to the association between excess body weight and type 2 DM, we found that both overweight and obesity were associated with higher prevalence of DM in univariate analysis. However, multivariate analysis demonstrated that only obesity and not overweight status was associated with higher risk of type 2 DM.…”
Section: Discussionmentioning
confidence: 99%
“…This number may double by the year 2025, because of population growth, ageing, unhealthy diets, obesity and sedentary lifestyles. In Greece, Katsilambros et al from the Aegaleo Study group reported that the prevalence of diabetes increased from 2.4% to 3.1% between 1974 and 1990 among middle-aged men and women [2]. More recent results from the ATTICA Study revealed that the prevalence of type 2 diabetes mellitus was 7.6% in middle-aged men and 5.9% in middle-aged women, living in urban and rural areas of the Athens metropolitan region in 2001 [3].…”
Section: Introductionmentioning
confidence: 98%
“…The increase in prevalence of DM is rapid, and IDF [4] estimates that people with diabetes, which were 350 million in 2011, will more than double and reach 552 million by 2030 [2].…”
Section: Introductionmentioning
confidence: 99%